$p=\dfrac{dz}{dx}$ and $q=\dfrac{dz}{dy}$

I have to find the complete integral solution of the Partial Differential Equation $$xp(1+q)=(y+z)q$$ $$ \Rightarrow f(x,y,z,p,q) = xp + xpq - yq - zq = 0$$ I am trying to solve it using Charpit equations : $$\dfrac{dx}{-f_p}=\dfrac{dy}{-f_q}=\dfrac{dz}{-pf_p-qf_q}=\dfrac{dp}{f_x+pf_z}=\dfrac{dq}{f_y+pf_z}$$

For the first and the last fraction: $f_p=x(1+q)$ and $f_y+pf_z=-q(1+q)$; which gives- $$\dfrac{dx}{-x(1+q)}=\dfrac{dq}{-q(1+q)}\Rightarrow \log(x) + \log(a) = \log(q)\Rightarrow q=ax.$$

From the given PDE and $q=ax$, we have $p=\dfrac{a(y+z)}{1+ax}.$

Now for the solution, we have to solve $dz=pdx+qdy \Rightarrow dz=\dfrac{a(y+z)}{1+ax}dx + axdy.$

I am not able to integrate $dz=\dfrac{a(y+z)}{1+ax}dx + axdy$. Any ideas on how to integrate this to get expression for $z$ in terms of $x$ and $y$?


Supposing that $q=ax$ and $p=\frac{a(y+z)}{1+ax}$ (I didn't check the simajinid'calculus). $$q=\frac{\partial z}{\partial y}=ax\quad\to\quad z=axy+\phi(x)$$

$$p=\frac{\partial z}{\partial x}=ay+\phi'(x)=\frac{a(y+axy+\phi(x))}{1+ax}$$ $$\phi'(x)=\frac{a\:\phi(x)}{1+ax}$$ $$\phi(x)=b(1+ax)$$ $$z(x,y)=axy+b(1+ax)$$ Of couse, this is only one particular solution, not the general solution of the PDE.


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.